2010
DOI: 10.2189/asqu.2010.55.2.255
|View full text |Cite
|
Sign up to set email alerts
|

Engendering Change: Organizational Dynamics and Workplace Gender Desegregation, 1975–2005

Abstract: We examine workplace-level sources of gender inequality to explore the link between organizational change and levels of workplace gender integration over time. To do so, we analyze the gender division of labor and key structural aspects of U.S. private-sector work establishments, using longitudinal data from the U.S. Equal Employment Opportunity Commission from 1975 to 2005. We find that women's presence in managerial positions is positively related to gender integration, as is both establishment size and grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
153
1
10

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(169 citation statements)
references
References 94 publications
5
153
1
10
Order By: Relevance
“…These studies show many of the relationships that organizational theorists of discrimination have hypothesized. Huffman et al (2010) demonstrate that progress particularly on gender desegregation has been driven by changes within firms over time rather than by the entry of integrated firms and the exit of segregated ones. Kalev et al's (2006) longitudinal study explores the policies behind such desegregation, and argues that policies that establish managerial responsibility through plans, formal committees and staff positions tend to increase managerial diversity; policies that raise awareness of diversity without assigning responsibility for outcomes do not.…”
Section: From Mechanisms To Effectsmentioning
confidence: 89%
See 3 more Smart Citations
“…These studies show many of the relationships that organizational theorists of discrimination have hypothesized. Huffman et al (2010) demonstrate that progress particularly on gender desegregation has been driven by changes within firms over time rather than by the entry of integrated firms and the exit of segregated ones. Kalev et al's (2006) longitudinal study explores the policies behind such desegregation, and argues that policies that establish managerial responsibility through plans, formal committees and staff positions tend to increase managerial diversity; policies that raise awareness of diversity without assigning responsibility for outcomes do not.…”
Section: From Mechanisms To Effectsmentioning
confidence: 89%
“…In addition to allowing us to "document desegregation" at a more fine--grained level than before (Tomaskovic--Devey et al 2006; see also Cohen, Huffman, and Knauer 2009), these data have been used to directly test the effects of different organizational practices on the promotion of women and minorities in the workplace (Kalev et al 2006;Kalev 2009;Huffman, Cohen, and Pearlman 2010). These studies set the current standard for research into the effects of limiting managerial discretion on employment discrimination.…”
Section: From Mechanisms To Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, it has been suggested that the search for gendered ghettos might extend not only to occupational specialisms but also to their fragmentation into specific roles and work tasks (Huffman, Cohen & Pearlman, 2010;Cockburn, 1988 Rendering the micropractices of gender segregation visible requires capturing individual experiences. Hence, the research took the form of semi-structured interviews.…”
Section: Methodsmentioning
confidence: 99%